2019
DOI: 10.1556/034.61.2019.3-4.5
|View full text |Cite
|
Sign up to set email alerts
|

Three new genera of the Ramalinaceae (lichen-forming Ascomycota) and the phenomenon of presence of ‘extraneous mycobiont DNA’ in lichen associations

Abstract: Phyllopsora swinscowii Timdal et Krog). The combination Biatora longispora (Degel.) Lendemer et Printzen is validated here. The new names Biatora vezdana for Lecania furfuracea Vĕzda and Coppinsidea vainioana for Lecidea sphaeroidiza Vain. are proposed. The phenomenon of presence of 'extraneous mycobiont DNA' in lichen association, i.e. DNA, belonging neither to mycobiont nor photobiont or to endophytic fungi is for the first time illustrated. So the presence of nrITS and mtSSU sequences of crustose lichen Cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…If there is evidence for a mixup, the safest way to obtain reliable data is repeating the PCR and sequencing steps, rather than trying to make sense of the existing data. Kondratyuk et al (2019) recently reported "extraneous mycobiont DNA", i.e., unexpected sequences corresponding to a particular lichen mycobiont presumably detected in the thallus of other lichens, e.g., of Biatora longispora (Ramalinaceae) in the thallus of Agonimia pacifica (Verrucariaceae). It is unclear whether these are the result of a laboratory mixup or of natural contamination of the underlying lichen thalli.…”
Section: A Quick Primer On Common Molecular Complicationsmentioning
confidence: 99%
“…If there is evidence for a mixup, the safest way to obtain reliable data is repeating the PCR and sequencing steps, rather than trying to make sense of the existing data. Kondratyuk et al (2019) recently reported "extraneous mycobiont DNA", i.e., unexpected sequences corresponding to a particular lichen mycobiont presumably detected in the thallus of other lichens, e.g., of Biatora longispora (Ramalinaceae) in the thallus of Agonimia pacifica (Verrucariaceae). It is unclear whether these are the result of a laboratory mixup or of natural contamination of the underlying lichen thalli.…”
Section: A Quick Primer On Common Molecular Complicationsmentioning
confidence: 99%
“…These results also appear to be congruent with Reese Naesborg et al . (2007), as well as Kondratyuk et al . (2019); in the latter the relationships between various genus-level clades were also weakly supported.…”
Section: Taxonomymentioning
confidence: 80%
“…However, the species was not included in recent molecular phylogenetic studies of generic delimitation within the broader Ramalinaceae ( e.g ., Kistenich et al 2018). It was included in the phylogenetic studies of Ramalinaceae by Kondratyuk et al . (2019) and transferred to the genus Coppinsidea S.Y.Kondr., E.Farkas and L.L}okös., but much of the underlying data for that study remains unpublished and the analyses were not fully described.…”
Section: Taxonomymentioning
confidence: 99%
“…Taxonomic notes: The genus Coppinsidea S. Y. Kondr., Farkas et L. Lőkös as monophyletic branch of the Ramalinaceae proposed to include nine species (Kondratyuk et al 2019b). Coppinsidea vernadskiensis is supposedly the next member of the same branch, while our efforts to get molecular data on this species were so far still unsuccessful.…”
Section: Descriptions Of Taxamentioning
confidence: 99%